Global discontents : conversations on the rising threats to democracy - Chomsky, Noam, (1928- ...) (Hamish Hamilton : Penguin Books, 2018)
Présentation de l'éditeur : "Global Discontents is an essential guide to geopolitics and how to fight back, from the world's leading public intellectualWhat kind of world are we leaving to our grandchildren? How are the discontents kindled today likely to blaze and explode tomorrow?From escalating climate change to the devastation in Syria, pandemic state surveillance to looming nuclear war, Noam Chomsky takes stock of the world today. Over the course of ten conversations with long-time collaborator David Barsamian, spanning 2013-2016, Chomsky argues in favour of radical changes to a system that cannot possibly cope with what awaits tomorrow. Interwoven with personal reflections spanning from childhood to his eighth decade of life, Global Discontents also marks out Chomsky's own intellectual journey, mapping his progress to revolutionary ideas and global prominence."